KEPEMIMPINAN KEPALA SEKOLAH PEREMPUAN DALAM UPAYA PENINGKATAN KINERJA GURU DI SDIT AT-TAQWA SURABAYA - LAILIYAH, KOMSATUN; , KARWANTO (Inspirasi Manajemen Pendidikan, 2019)
Abstract: This study aims to describe and analyze 1) the style of female principals in SD-At-Taqwa Surabaya, 2). Describe the efforts made by the principal in an effort to improve teacher performance at SDIT At-Taqwa Surabaya. This study uses a qualitative approach. Research conducted by researchers is 1) Pre-Field Phase; 2) Stages of Field Activities; 3) Intensive analysis stages .The results of the study can be explained as follows: (1) The leadership style of female principals is inferred from several aspects that have been determined by the researcher, namely: (a) The principals daily behavior is firm, disciplined and democratic. (b) Decision making by open principals (c) Supervision is carried out by the principal to the teacher through supervision and class visits. (d) Development of schools by participating in inter-school competitions, infrastructure development (e) Principals are patient, friendly, open people (2) Efforts made by female principals in efforts to improve teacher performance include: (a) Development of teacher competencies done by involving teachers in training, coaching, teacher working groups (KKG), or workshops. (B) The disciplinary guidance carried out by the principal for the teacher is through memberchek and also the deadline to collect the learning implementation plan. (c) The principal provides motivation in the form of facilitating the activities carried out by the teacher. (d) Awards Giving minimal praise in the form of thanksgiving and appreciation or appreciation for achievements made by the teacher capable of encouraging teacher performance. Key words: Style of Womens Leadership, Teacher Performance Abstrak: Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis 1) gaya kepala sekolah perempuan di SDIT At-Taqwa Surabaya, 2) Mendeskripsikan Usaha-usaha yang dilakukan kepala sekolah dalam upaya peningkatan kinerja guru di SDIT At-Taqwa Surabaya. Penelitian ini menggunakan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa : (1) Gaya kepemimpinan kepala sekolah perempuan disimpulkan dari beberapa aspek yang telah peneliti tentukan yaitu : (a) Perilaku keseharian kepala sekolah menerapkan sikap tegas disiplin sekaligus demokratis. (b) Pengambilan keputusan kepala sekolah terbuka (c) Pengawasan yang dilakukan kepala sekolah kepada guru yaitu melalui supervisi dan kunjungan kelas. (d) Pengembangan sekolah dengan mengikuti perlombaan-perlombaan, pengembangan sarana prasarana. (e) Kepala sekolah merupakan orang yang penyabar, dan Kepala sekolah merupakan kepala sekolah yang ramah (2) Usaha-usaha yang dilakukan kepala sekolah perempuan dalam upaya peningkatan kinerja guru, meliputi : (a) Pengembangan kompetensi guru dilakukan dengan mengikutsertakan guru dalam pelatihan-pelatihan, pembinaan, KKG, ataupun workshop. (b) Pembinaan disiplin yang dilakukan kepala sekolah kepada guru adalah melalui checklock dan juga deadline pengumpulan RPP (c) Kepala sekolah memberikan motivasi berupa memfasilitasi kegiatan yang dijalankan oleh guru. (d) Penghargaan, pemberian pujian minimal dalam bentuk ucapan terimakasih serta penghargaan atau apresiasi atas prestasi yang dilakukan oleh guru mampu mendorong untuk meningkatkan kinerja guru. Kata kunci: Gaya Kepemimpinan Perempuan, Kinerja Guru